The Effect of Tax Planning, Profitability and Leverage on Firm Value in Food and Beverage Companies on the Indonesia Stock Exchange from 2017 To 2021 - Tri Aryantara Saputra; Ibnu Fajaruddin (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the influence of tax planning, profitability and leverage on firm value. This study uses a quantitative approach in the form of financial statements of food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique used in this study used a purposive sampling approach, the number of samples used in this study were 90 samples. The results of testing the first hypothesis (H1) show that tax planning has no effect on firm value. The results of testing the second hypothesis (H2) show that profitability has an effect on firm value. The results of testing the third hypothesis (H3) show that leverage has an effect on firm value. The results of testing the fourth hypothesis (H4) show that Tax Planning, Profitability and Leverage have an effect simultaneously on Firm Value. In the following, there are some research limitations found in this study, namely in this study, the limitation of the problem lies in tax planning, profitability and leverage on firm value. In this study, researchers used food and beverage companies on the Indonesia Stock Exchange from 2017 to 2021. The results of this study can be used as one of the considerations in making decisions to invest. As for the company, the results of this study are expected to be able to evaluate and increase the value of the company.